Antioxidative and Anti-Inflammatory Protective Effects of β-Caryophyllene against Amikacin-Induced Nephrotoxicity in Rat by Regulating the Nrf2/AMPK/AKT and NF-κB/TGF-β/KIM-1 Molecular Pathways. (26th August 2022) - Rajab, Bodour S.; Albukhari, Talat A.; Khan, Anmar A.; Refaat, Bassem; Almehmadi, Samah J.; Nasreldin, Nani; Elshopakey, Gehad E.; El-Boshy, Mohamed
Abstract : Herein, the molecular pathogenic pathways implicated in renal injury triggered by amikacin (AK), together with the alleviating actions of β -caryophyllene (BCP), were investigated. Adult male Wistar rats (n = 32 ) were disseminated to the four following groups (n = 8 /group): normal group, positive control animals (PC) that received AK intraperitoneal injections for 14 days (500 mg/kg/day), and rats that received AK simultaneously with small (200 mg/kg/day) and high doses (400 mg/kg/day) of BCP. The PC renal tissues revealed abnormal histology alongside increased apoptosis and significantly elevated serum creatinine and urea with marked proteinuria and oliguria relative to the normal rats. Moreover, renal tissues from the PC animals also showed substantial upregulations in NF- κ B/TGF- β /KIM-1, whilst Nrf2/AMPK/AKT/PCNA declined, at the gene and protein levels in comparison to the normal rats. Additionally, the levels of markers of oxidative stress (MDA/H2 O2 /protein adducts) and inflammation (TNF- α /IL-1 β /IL-6/IL-18/TLR/HSP25) were substantially higher in the PC renal specimens, whereas the antioxidants (GSH/GPx/SOD1/CAT) and interleukin-10 decreased, relative to the NC group. Both BCP protocols improved the biochemical markers of renal functions, alleviated renal histopathology and apoptosis, and decreased NF- κ B/TGF- β /KIM-1 alongside the concentrations of oxidative stress and proinflammatory markers, whilst promoting Nrf2/AMPK/AKT/IL-10/PCNA and the targeted antioxidants. However, the improving effects in the high-dose regimen were markedly stronger than those observed in animals treated with low dose of BCP. In conclusion, the present report is the first to connect NF- κ B/TGF- β /KIM-1 proinflammatory and Nrf2/AMPK/AKT antioxidative stress pathways with the pathogenesis of AK-induced nephrotoxicity. Additionally, the current report is the first to disclose alleviating activities for BCP against AK-triggered nephrotoxicity by modulating multiple antioxidative stress with anti-inflammatory molecular pathways.